2007
DOI: 10.2320/matertrans.mer2007122
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Prediction of Voids Formation in a Growing Nickel Oxide Scale at 1373 K

Abstract: Voids which form in oxide scales strongly influence the mechanical properties of the scale and the adherence between the metal substrate and the scale. The purpose of this study is to demonstrate a method for quantitative estimation of voids formation in NiO scale, and compare the microstructure of the scale formed on nickel at 1373 K with the estimation.Calculations of ion fluxes and their divergence in NiO scales can predict the annihilation of the oxides which mostly occurs in the vicinity of the metal/oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Grids of uniformed size were traced on each images and area fraction of voids in the scale was measured. It was ass to the cross-sectional area fraction of voids in the scale applied by Akiba et al [11] substrate at 1373 K. Figure 2 shows an example of an area of a sample's 4 spots being analyzed to determine the main SEM micrograph shows the spots for EDX analysis.…”
Section: Fig 3: Schematics Of Samples After Being Crossmentioning
confidence: 99%
“…Grids of uniformed size were traced on each images and area fraction of voids in the scale was measured. It was ass to the cross-sectional area fraction of voids in the scale applied by Akiba et al [11] substrate at 1373 K. Figure 2 shows an example of an area of a sample's 4 spots being analyzed to determine the main SEM micrograph shows the spots for EDX analysis.…”
Section: Fig 3: Schematics Of Samples After Being Crossmentioning
confidence: 99%
“…Figure 13 shows the parabolic plots of the scale thickness of both NiO scale and CoO scale formed on nickel and cobalt in Ar-21 %O 2 at 1373 K, which was reported by the present authors. 3,4) The growth rate of CoO scale on cobalt is larger than that of NiO scale on nickel. It indicates that the oxygen consumption rate for the oxidation of cobalt is larger than that of nickel.…”
Section: Measurement Of Thickness Of Gas Boundary Layermentioning
confidence: 99%
“…Present authors 3,4) have demonstrated the prediction of the voids formation in the scales of NiO and CoO formed in high temperature oxidation of nickel and cobalt at 1373 K, and have predicted that the voids in the oxide scale form mainly in the vicinity of the metal/oxide interface in a quantitative manner. These predictions are in good agreement with the morphology that is experimentally observed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations